FIELD TRIALS OF A SLOW-RELEASE COPPER MOLLUSCICIDE IN KHUZESTAN, SOUTH-WEST OF IRAN - J. Massoud; A. Mansoorian (Tehran University of Medical Sciences, 1986)
In the field trials of slow-release nollusicide, copper content McCkechnie Chemical Inc. 30 cuso4 5H2o or 7.5 cupellet/sinking material 7 days release life were tested against the common aquatic snails bulinus truncatus, Physa acuta and Lymnaea gedrosiana in stagnant water bodies in Khuzestan province, south-west of Iran. Snail densities before treatment and 7 days after mollucicide application were determined by 10 deep nets per man. The results of the present trials as shown on tables 1, 2, 3 and 4 indicate that the effect of different concentration of copper based slow-relased mollnscicide (7.55 cu) is different for different species of aquatic snails. The maximum concentration to achieve 100 ppm. Mortality rate was 20 ppm for Lymnaea gedrosiana, 100ppm for physaacuta and over 120ppm for Bulinus truncatus. The high susceptibility of lymnaea snails to the chemical is very promising for the control of livestock trematodes infection in this area.